Do lower air or water temperatures limit the southern distribution of the white mangrove Laguncularia racemosa in South America? - Santos Borges, Jaqueline (2019)
Rising temperatures due to climate change are expected to drive shifts in species composition, phenological patterns and the productivity of mangrove trees. During early life history stages, such as dispersal and settlement, temperature may affect the survival of propagules and, consequently, drive the distribution of mangrove species. The aim of this work was to evaluate whether low water and air temperatures experienced by propagules during the dispersal and settlement stages, respectively, limit the latitudinal distribution of the white mangrove Laguncularia racemosa. Based on the distribution range of L. racemosa, we investigated four water and air temperatures: 10, 15, 20 and 25 °C. First, we evaluated the effect of seawater temperature on the buoyancy time of propagules. Then we tested the effect of seawater temperature and buoyancy time (24, 48, 72 and 96 h) on the germination rate of L. racemosa. Finally, we evaluated the effect of air temperature (10, 15, 20 and 25 °C) on the germination of propagules during the stranded stage. The propagules in higher water temperatures (20 and 25 °C) submerged faster than in lower temperatures (10 and 15 °C). The percentage germination of propagules in water temperatures of 20 and 15 °C was higher than those in 25 and 10 °C. However, the percentage germination was greater than 70%, regardless of the water temperature or buoyancy time tested. Furthermore, the percentage germination of propagules in air temperatures of 25 and 20 °C was higher (above 70%) than in air temperatures of 15 and 10 °C (below 50%). Lower water temperature increased the dispersal time of propagules, but it was not crucial to the germination rate of L. racemosa, regardless of the buoyancy time of propagules. In contrast, a lower air temperature reduced the germination of propagules during the stranded stage. Therefore, water temperature is not a limiting factor for the success of L. racemosa during the dispersal stage, however, we found that the mangrove tree is highly sensitive to air temperature during its stranded stage. We hypothesized that the increased buoyancy time of propagules during lower temperatures is an adaptive advantage, which allows L. racemosa to be transported to warmer areas or to tolerate cold temperatures for longer periods before settlement.